Phenotypic Detection of Extended Spectrum Beta-Lactamases in Uro-pathogens. An Experience from Qazi Hussain Ahmed Medical Complex, Nowshera: ESBL - Hamzullah Khan, Hamzullah Khan (Journal of Rawalpindi Medical College, 2020)
Objectives: To determine the phenotype and frequency of Extended Spectrum Beta-Lactamase in Uro-pathogens in a tertiary care hospital of Nowshera. Material and methods: This Prospective cohort study was performed in the clinical pathology laboratory of Qazi Hussain Ahmed Medical Complex (QHAMC) Nowshera from 1st Jan 2019 to 30th May 2019. Relevant information was recorded on a predesigned proforma prepared as per CLSI Recommendation for data collection. Results: A total of 192 urine samples were received for Culture and sensitivity. Out of which 56 cases were ESBL phenotypically positive (29.16%). 39(69.9%) were females and 17(30.4%) were males. The age range of the patient was from 3 months to 63 years of age, with a mean age of 30 years with +5.4 SD Frequency of ESBL producing uro-pathogens was; 51(91%) E-Coli, 4(7.1%) Klebsiella pneumonia and 1(1.8%) Proteus mirabilis. Out of 39 ESBL producing uro-pathogen in Female gender, E Coli-ESBL producing strains were isolated in 35 patients, Klebsiella Pneumonia in 3 patients and one case was of Proteus mirabilis-ESBL. In the male gender, 17 cases with E Coli-ESBL were reported and one case of Kliebsilla Pneumonia ESBL. Conclusion: The prevalence of ESBL producers in the present study was quite alarming and challenging to the clinician in treating urinary tract infections. These types of resistant infections are a challenge to treat and a public health threat that needs accumulative response through advocacy, communication, and social mobilization.